Tinjauan Hukum Islam terhadap Praktik Tradisi Nyorog di Desa Citrajaya Kabupaten Subang - Ageung Nur Inayah; Siska Lis Sulistiani; Ilham Mujahid (Bandung Conference Series: Islamic Family Law, 2022)
Abstract. A tradition cannot be separated from the village community. For one thing, it was the nyorog tradition in Citrajaya village which is held at the time of the wedding celebration. At first nyorog tradition was a good activity, namely silaturahmi by bringing food without expecting more rewards for what has been given. Along with the development of the times, the practice of nyorog tradition nowadays is put forward to be rewarded for the gifts that are given to the recipients of sorogan, causing the recipient to feel burdened with the food they receive. The results of the research, it can be concluded that the practice of nyorog tradition in the Village of Citrajaya now is not in accordance with the provisions of Islamic law and can be categorized into urf fasid. Abstrak. Suatu tradisi tidak dapat dipisahkan dari masyarakat desa. Salah satunya, yaitu tradisi nyorog di Desa Citrajaya yang dilaksanakan ketika mengadakan walimah pernikahan. Pada mulanya tradisi nyorog merupakan suatu kegiatan yang baik, yaitu silaturahmi dengan membawa makanan tanpa mengaharap imbalan dari pihak yang diberi sorogan. Namun, seiring perkembangan zaman praktik tradisi nyorog sekarang lebih mengedepankan rasa ingin dibalas sehingga menyebabkan pihak penerima merasa terbebani dengan makanan yang diterimanya. Dari hasil penelitian dapat disimpulkan, bahwa praktik tradisi nyorog yang berlaku sekarang di Desa Citrajaya tidak sesuai dengan ketentuan dalam hukum Islam dan dapat dikategorikan kedalam urf fasid.